2009
DOI: 10.1111/j.1559-1816.2009.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Positive Illusions Versus Shared Reality Models of Relationship Satisfaction Among Gay, Lesbian, and Heterosexual Couples

Abstract: According to the positive illusions model (Murray, Holmes, & Griffin, 1996a), people in romantic relationships are more satisfied when they view their partners more favorably than the partners see themselves. By contrast, shared reality theory (Hardin & Conley, 2001) emphasizes the benefits of perceiving a partner as the partner sees himself or herself. We analyzed archived data from the American Couples Study (Blumstein & Schwartz, 1983) to test the applicability of the positive illusions model to gay and les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…Idealization and positive illusions are positively related to satisfaction of individuals in different-sex (Murray et al, 1996a(Murray et al, , 1996b and same-sex (Conley, Roesch, Peplau, & Gold, 2009) relationships, commitment (Rusbult et al, 2001), and love (Miller, Niehuis, & Huston, 2006) in cross-sectional studies. Longitudinal evidence shows that illusory beliefs are related to lower levels of breakup (Le et al, 2010;Murray et al, 1996b) and changes in love (Miller et al, 2006).…”
Section: Individual Threat-mitigation Maintenance Processesmentioning
confidence: 99%
“…Idealization and positive illusions are positively related to satisfaction of individuals in different-sex (Murray et al, 1996a(Murray et al, , 1996b and same-sex (Conley, Roesch, Peplau, & Gold, 2009) relationships, commitment (Rusbult et al, 2001), and love (Miller, Niehuis, & Huston, 2006) in cross-sectional studies. Longitudinal evidence shows that illusory beliefs are related to lower levels of breakup (Le et al, 2010;Murray et al, 1996b) and changes in love (Miller et al, 2006).…”
Section: Individual Threat-mitigation Maintenance Processesmentioning
confidence: 99%
“…The 2M3G APIM is designed for 2M3G data. Typical examples are gay, lesbian, and heterosexual couples (e.g., Conley, Roesch, Peplau, & Gold, ) or male, female, and mixed‐gender dizygotic twins. The key of this model is that there is a dichotomous group variable measured in each dyad member, which is gender in gay, lesbian, and heterosexual couples and male, female, and mixed‐gender twins.…”
Section: The Mmmg Apimmentioning
confidence: 99%
“…To the best of our knowledge, a study by Conley and colleagues () is the sole study of partner accuracy among same‐sex couples. Conley and colleagues speculated that due to stigmatization (Lehmiller & Agnew, , ), gay and lesbian partners may value authenticity and accurate knowledge of each other more than they value uninformed positivity.…”
Section: The Relationships and Sex Lives Of Same‐sex And Heterosexualmentioning
confidence: 99%
“…Moreover, the strength of these illusions predicted the overperceivers' sexual satisfaction. Conley and colleagues () found that among gay men and lesbians (as well as among heterosexuals), people tended to view their partners more positively than the partners viewed themselves, and people who idealized their partners were more satisfied in their relationships. By examining the role of positive illusions in an understudied population, this study addresses an important gap in the literature.…”
Section: The Relationships and Sex Lives Of Same‐sex And Heterosexualmentioning
confidence: 99%
See 1 more Smart Citation